Synchronous association of gastrointestinal stromal tumors of the jejunum and sigmoidal adenocarcinoma: A case report - Belghali, Houssam; Belhaj, Anas; Ibn Majdoub, Karim; Taughrai, İmane; Mazaz, Khalid (Journal of Surgery and Medicine, 2019)
The association of agastrointestinal stromal tumor (GIST) with an epithelial tumor of the digestivetract is very rare and frequently discovered by chance during the surgicaltreatment of digestive carcinoma. These tumors developed from the mesenchyme areknown to have a good prognosis given their low malignancy potential. Thepossibility of a genetic mutation or an oncogenic agent capable of inducingtumors of different histotypes seems less plausible but it is not to bediscarded. We report the case of a 74-year-old patient, operated for a sigmoidadenocarcinoma, with incidental discovery of a small bowel tumor whosehistology confirmed the diagnosis of a GIST.